Dangerous Stories: Narrative Theory and Critique in a Post-Truth World - Whitehead, Jason E. (Narrative Works, 2022)
Political and legal scholars use narrative theory to study everything from the framing of policy arguments to the telling of tort tales to the construction of political consciousness. Such scholarship often relies on post-positivist theories that problematize the empirical validity of narratives. But the stories told by many recent movements in American politics—such as Christian nationalism, “the Big Lie,” and Covid-19 conspiracy theories—so distort empirical reality that they endanger liberal norms and values, not to mention human lives. Scholars who ordinarily eschew objective narrative validity may nevertheless want to critique and challenge such stories on empirical grounds. This article investigates the options available to narrative scholars studying these types of stories. First, I survey different approaches to narrative, drawn from philosophy, rhetorical studies, critical feminist theory and critical race theory. Second, I highlight the resources and strategies devised by scholars who use these approaches to analyze other empirically problematic and socially dangerous narratives, especially how they have combined post-positivist commitments with concerns for truth and justice. Finally, I make suggestions for how scholars can better study and critique the political and legal narratives associated with the Trump era.